JURIDICAL REVIEW OF CONSUMER PROTECTION IN GUARANTEEING CONSUMER RIGHTS IN E-COMMERCE TRANSACTIONS - Nurani, Juli; Indawati, Indawati; Wahyuningati, Edi; Prameswari, Marchella Arnaz (jfpublisher, 2024)
The rapid advancement of information technology has transformed trade, especially with the rise of e-commerce, which accelerates transactions and promotes the global digital economy. However, this shift has also introduced risks for consumers, such as receiving items that do not match advertisements or encountering scams, where businesses fail to deliver purchased goods. In Indonesia, consumer protection laws, particularly Law No. 8/1999 on Consumer Protection and the amended Law No. 11/2008 on Electronic Information and Transactions, aim to safeguard consumers and address these challenges amid the evolving e-commerce landscape. This research aims to examine the juridical aspects of consumer protection in e-commerce transactions in Indonesia, focusing on the legal framework governing consumer rights, challenges in the implementation of the law, as well as proposed solutions to improve the consumer protection system. This research is a normative legal research to address a legal problem by determining legal principles and relevant legal rules as a solution to legal problems that become research objects. The research findings indicated that consumer legal protection, as established by the 1999 Consumer Protection Law, protects consumers against scams, misleading terms, and product discrepancies, especially in e-commerce, to ensure trust, security, and fair practices amid the rise of digital transactions. Furthermore, effective legal protection of consumers is necessary to overcome various unfair practices in transactions, especially in this evolving digital era.